Disclaimer of Political Rights As An Effort to Eradicate Corruption - Yuningsih, Henny; Nashriana, Nashriana; Febriani, Indah; Rumesten, Iza (Faculty of Law, Universitas Lampung, 2024)
Corruption is an extraordinary crime, so extraordinary methods are also needed to prevent and eradicate this crime. The imposition of serious crimes is one of the ways needed to eradicate them, then new punitive breakthroughs are also needed in order to provide a sense of deterrence and fear to both the perpetrators and the community. Several cases that have been decided during the trial of corruption at the first level, among others, are on behalf of the accused, Inspector General. Djoko Susilo in the corruption case of the procurement of a driving license (SIM) simulator tool, the KPK Public Prosecutor demanded additional crimes of revoking the right to vote and vote in general elections and public office (political rights), and the panel of judges granted the demands at the appeal level. This additional punishment is regulated in article 35 of the Criminal Code in conjunction with article 18 paragraph (1) of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning Corruption. This research uses normative legal research methods, supported by primary, secondary and tertiary legal sources. With descriptive qualitative analysis.The problem with this additional punishment for depriving political rights is how to apply this additional punishment for depriving political rights in the prevention and eradication of corruption, because of course the KPK has strong reasons why this additional punishment is included as a punishment for perpetrators of corruption.